Analisis efektivitas penggunaan media nearpod dalam meningkatkan hasil belajar bahasa indonesia disekolah dasar: tinjuan literatur review - Violita, Febby; Irawan, Windo Dicky (Universitas Pendidikan Ganesha, 2025)
Low student learning outcomes in this topic are often caused by less interactive teaching strategies and limited use of up-to-date learning resources. This study aims to analyze the use of Nearpod media in improving Indonesian language learning outcomes in elementary schools. The method used is a Systematic Literature Review (SLR). Data was collected by systematically searching academic databases such as Google Scholar, Scopus, and Science Direct. The analysis technique uses qualitative and quantitative analysis. The analysis results show that Nearpod can significantly increase student engagement, conceptual understanding, and learning outcomes. Interactive features in Nearpod, such as quizzes, polls, and discussions, provide a more interesting and practical learning experience than conventional methods. Factors that support the success of Nearpod implementation include teacher readiness in integrating technology and accessibility of war. This study confirms that Nearpod has excellent potential as an innovative learning media in Indonesian language subjects in elementary schools. The study's conclusion shows that Nearpod is a very efficient educational tool in improving academic achievement in the Indonesian language in elementary schools; there is a significant increase in motivation and understanding of student learning concepts. This success is seen in the increase in learning outcome scores and in the way this media creates more interactive and enjoyable learning. This literature implies that using Nearpod can improve overall Indonesian language learning outcomes.